The Students’ Attitude toward English Instruction on the EFL Students’ Speaking Class - Rafiqa; Nirma Paris (EDUVELOP, 2021)
Abstract: In general, an English teacher uses bilingual method in teaching process. However, a native English teacher uses English only in the class. Due to the new atmosphere faced by the students, the present study aimed to investigate the students’ attitude toward English instruction on the EFL students’ speaking class. This current study employed a quantitative method and it was designed as a descriptive research. The participants of this study were 156 students of English Study Program enrolled at Speaking class, Faculty of Tarbiyah, State Islamic Institute of Parepare. A 20-item survey questionnaire related to the students’ attitude toward English instruction with a five point likert scale was assigned to obtain the data from the participants. The results of the study revealed that the students have a positive attitude toward English instruction. They agreed with teaching English by using English instruction. The students’ cognitive and affective responses showed that the students believed that English instruction could improve the students’ abilities at intermediate level. Furthermore, the students’ cognitive responses indicated that the students’ vocabularies and grammatical knowledge improved. The use of English instruction also gave the students an opportunity to learn pronunciation from the native English teacher. While, the results of affective responses indicated that the students liked to study using English instruction and they were motivated to speak in English.